The neutralising and stimulatory effects of antimicrobial peptide LL-37 in human gingival fibroblasts. (April 2023) - Lappin, MJ; Dellett, M.; Mills, KI; Lundy, FT; Irwin, CR
Abstract: Objectives: To investigate the effects of LL-37, a broad spectrum antimicrobial peptide expressed in periodontal tissues, on human gingival fibroblast responsiveness to microbial challenge and to explore the direct effects of LL-37 on human gingival fibroblasts. Design: The effect of LL-37 on bacterial lipopolysaccharide-induced expression of Interleukin (IL-6) and chemokine C-X-C motif ligand (CXCL) 8 was determined by enzyme linked immunosorbent assay (ELISA). LL-37′s influence on bacterial lipopolysaccharide-induced IκBα degradation was investigated by western blot. DNA microarray analysis initially determined the direct effects of LL-37 on gene expression, these findings were subsequently confirmed by quantitative polymerase chain reaction and ELISA analysis of selected genes. Results: Bacterial lipopolysaccharide-induced IL-6 and CXCL8 production by human gingival fibroblasts was significantly reduced in the presence of LL-37 at concentrations in the range of 1–10 µg/ml. LL-37 led to a reduction in lipopolysaccharide-induced IκBα degradation by Escherichia coli lipopolysaccharide and Porphyromonas gingivalis lipopolysaccharide (10 µg/ml). LL-37 (50 µg/ml) significantly altered the gene expression of 367 genes in human gingival fibroblasts by at least 2-fold. CXCL1, CXCL2, CXCL3, Interleukin-24 (IL-24), CXCL8, Chemokine (C-C motif) Ligand 2, and Suppressor of Cytokine Signalling 3 mRNA were significantly upregulated by LL-37. LL-37 also significantly stimulated expression of CXCL8, hepatocyte growth factor and CXCL1 at the protein level. Conclusion: LL-37 plays an important regulatory role in the immunomodulatory activity of gingival fibroblasts by inhibiting lipopolysaccharide -induced expression of inflammatory cytokines and directly stimulating the expression of an array of bioactive molecules involved in inflammation and repair. Highlights: The cathelicidin peptide LL-37 alters gene expression in human gingival fibroblasts. LL-37 significantly upregulates CXCL1, CXCL8 and Interleukin 24 mRNA expression. LL-37 stimulates protein production of CXCL1, CXCL8 and hepatocyte growth factor. LL-37 reduces lipopolysaccharide-induced expression of Interleukin 6 and CXCL8. LL-37 reduces lipopolysaccharide-induced IκBα degradation in gingival fibroblasts.